Intravenous magnesium sulfate for postoperative analgesia after abdominal hysterectomy under spinal anesthesia: a randomized, double-blind trial - Márcio Luiz Benevides; Danielle Carvalho Fialho; Daiane Linck; Ana Luiza Oliveira; Dennis Henrique Vieira Ramalho; Marília Marquioreto Benevides (Brazilian Journal of Anesthesiology, 2021)
Background and objectives: Abdominal Hysterectomy (AH) is associated with significant inflammatory response and can result in moderate to severe postoperative pain. This study aimed to evaluate the efficacy of magnesium infusion in reducing postoperative pain and analgesic consumption after AH under spinal anesthesia with Intrathecal Morphine (ITM). Method: Eighty-six patients were included in this clinical, controlled, randomized, double-blind study. Patients received in Group Mg, MgSO4 50 mg kg−1 for 15 minutes followed by 15 mg kg−1 h−1 until the end of the surgery; and in Group C, (control) the same volume of isotonic saline. Both groups received 100 μg of ITM. All patients received dipyrone + ketoprofen intraoperatively and postoperatively, and dexamethasone intraoperatively only. We evaluated the intensity of pain, tramadol consumption, and adverse events 24 hours postoperatively. Results: Serum magnesium concentrations were higher in Group Mg at the end, and one hour after the operation (p = 0.000). Postoperative pain scores were reduced in Group Mg at 6 hours at rest and on movement (p < 0.05). Tramadol consumption did not show a statistically significant difference between Group Mg and Group C (15.5 ± 36.6 mg and 29.2 ± 67.8 mg respectively, p = 0.53). Hemodynamic variables, the incidence of pruritus, nausea, and vomiting were similar in the two groups. Conclusion: Infusion of MgSO4 during AH undergoing spinal anesthesia with ITM reduced at 6 hours at rest and on movement. More studies should be performed to evaluate the potential antinociceptive effect of MgSO4 in scenarios where a multimodal analgesia approach was employed.